REVIEW ARTICLE: SOLUBILITY ENHANCEMENT BY SOLID DISPERSION - Patil, A. N.; Shinkar, D. M.; Saudagar, R. B. (International Journal of Current Pharmaceutical Research, 2017)
Enhancement of solubility, dissolution rate and bioavailability of the drug is a very challenging task in drug development, nearly 40% of the new chemical entities currently being discovered are poorly water soluble drugs. The solubility behaviour of the drugs remains one of the most challenging aspects in formulation development. This results in important products not reaching the market or not achieving their full potential. Solid dispersion is one of the techniques adopted for the formulation of such drugs and various methods are used for the preparation of solid dispersion. Solid dispersion is generally prepared with a drug which is having poor aqueous solubility and hydrophilic carrier. This article review various methods and concept of solid dispersion, criteria for drug selection, advantage and disadvantage, characterization, and application.